2009
DOI: 10.1128/jcm.00847-09
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Peritonitis Caused byKocuria marinain Patients Undergoing Continuous Ambulatory Peritoneal Dialysis

Abstract: Kocuria spp. are members of the Micrococcaceae family that are frequently found in the environment and on human skin. Few human infections have been reported. We describe what appear to be the first two cases of Kocuria marina peritonitis in patients undergoing continuous ambulatory peritoneal dialysis. CASE REPORTS Case 1.A 57-year-old man was admitted to the emergency department because of turbid dialysis effluent for 1 day. He had end-stage renal disease as a result of diabetic nephropathy and had been unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 12 publications
0
58
0
Order By: Relevance
“…Another member of the genus, K. kristinae, has also been reported to cause a catheter-related bacteremia in patients with ovarian cancer (3) or acute cholecystitis (14). In 2009, two cases of peritonitis caused by K. marina were reported by Lee et al (12). More recently, in 2010, Lai et al (11) reported catheter-related bacteremia and infective endocarditis caused by Kocuria sp., whereas Tsai et al (27) reported a K. varians infection associated with brain abscess.…”
Section: Originally Deposited As Sarcina Lutea and Later Redesimentioning
confidence: 99%
“…Another member of the genus, K. kristinae, has also been reported to cause a catheter-related bacteremia in patients with ovarian cancer (3) or acute cholecystitis (14). In 2009, two cases of peritonitis caused by K. marina were reported by Lee et al (12). More recently, in 2010, Lai et al (11) reported catheter-related bacteremia and infective endocarditis caused by Kocuria sp., whereas Tsai et al (27) reported a K. varians infection associated with brain abscess.…”
Section: Originally Deposited As Sarcina Lutea and Later Redesimentioning
confidence: 99%
“…Indeed, it has been reported that Kocuria can cause bacteraemia in chronically ill patients with malignancies or in immunosuppressed states (Basaglia et al, 2002;Martinaud et al, 2008). Kocuria infection has been linked to cases of peritonitis associated with peritoneal dialysis (Altuntas et al, 2004;Lee et al, 2009;Meletis et al, 2012), acute cholecystitis (Ma et al, 2005), catheter-related bacteraemia (Dunn et al, 2011;Lai et al, 2011;Moissenet et al, 2012), infective endocarditis (Lai et al, 2011) and brain abscesses (Tsai et al, 2010). Here, we describe the first known case of Kocuria dacryocystitis in an immunocompetent patient.…”
Section: Introductionmentioning
confidence: 75%
“…One patient experienced 3 episodes of relapsing peritonitis attributable to K. varians; another had 2 episodes of relapsing peritonitis attributable to the same Kocuria species. In total, 9 PD patients with end-stage renal disease were reported to experience peritonitis caused by Kocuria species (4,5,(8)(9)(10)(11)(12)(13). In all the Kocuria peritonitis episodes, no ultrafiltration problems were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the patient who experienced 3 relapsing peritonitis episodes with K. varians received IP cefazolin for 10 days for the first episode, IP cefazolin for 7 days JANUARY 2015 -VOL. 35, NO.1 PDI after peritonitis relapse, and IP cefazolin for 14 days after the second relapse, which is the formal suggested regimen (4). Recommendations for avoidance of Kocuriaspecies peritonitis follows the general consensus guidelines for the prevention of catheter-related infections and peritonitis in pediatric patients receiving PD (7).…”
Section: Discussionmentioning
confidence: 99%